2019
DOI: 10.1039/c9cc02134e
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis of S-doped carbon with weak polysulfide adsorption enhances lithium–sulfur battery performance

Abstract: S-doped carbon boosts the conversion of lithium polysulfides by electrocatalysis as revealed by kinetic analysis and theoretical calculation, which suppresses the serious polarization effect and thus enhances the Li–S battery performance, despite its weak adsorption to polysulfides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…[1] Amongavariety of rechargeable batteries, lithium-sulfur batteries have attracted extensive attention in the past few years. [2] Comparedw ith the mosta dvanced commercial lithium ion batteries, lithiumsulfur batteries not only have higher theoretical specific capacity (1672 mAh g À1 )a nd energy density (2600 Wh kg À1 ), but also have the advantages of low cost and environmental friendliness. [3][4][5] Although the lithium-sulfur batteries have the potential to be expected as the next-generationo fr echargeables ystems, they still face av ariety of challenges, such as the "shuttle effect" of high order polysulfides, [6] the poor electronic conductivity of sulfur and lithiums ulfides (Li 2 S 2 ,L i 2 S) [7] andt he large sulfur volumetrice xpansion during cycling, [8] which result in rapid capacityf ade, low utilization of the active materiala nd poor Coulombic efficiency.…”
mentioning
confidence: 99%
“…[1] Amongavariety of rechargeable batteries, lithium-sulfur batteries have attracted extensive attention in the past few years. [2] Comparedw ith the mosta dvanced commercial lithium ion batteries, lithiumsulfur batteries not only have higher theoretical specific capacity (1672 mAh g À1 )a nd energy density (2600 Wh kg À1 ), but also have the advantages of low cost and environmental friendliness. [3][4][5] Although the lithium-sulfur batteries have the potential to be expected as the next-generationo fr echargeables ystems, they still face av ariety of challenges, such as the "shuttle effect" of high order polysulfides, [6] the poor electronic conductivity of sulfur and lithiums ulfides (Li 2 S 2 ,L i 2 S) [7] andt he large sulfur volumetrice xpansion during cycling, [8] which result in rapid capacityf ade, low utilization of the active materiala nd poor Coulombic efficiency.…”
mentioning
confidence: 99%
“…46,47,55,56 In a recent work, Du et al reported that S-doped carbon acts as a metal-free electrocatalyst that enhances the conversion kinetics of poly-suldes, which leads to a superior performance. 48 Remarkably, the porous carbon hosts presented in this work meet the requirements of a good metal-free electrocatalyst: (i) a high degree of heteroatom doping (>5.5% S) and (ii) good electrical conductivity (>3 S cm À1 ). The combination of both properties could explain the good electrochemical performance observed in our experiments.…”
Section: Electrochemical Performance Of the Sulfur/carbon Composites mentioning
confidence: 84%
“…† The importance of the sulfur attached to the carbon lies in the fact that it can contribute to controlling the migration of polysulde species and, in this way, improve the electrochemical performance of the Li-S battery. [46][47][48]…”
Section: View Article Onlinementioning
confidence: 99%
“…The presence of elemental sulfur (164.3 eV) is discarded since the carbon host was recovered by thermally treating the S/C composite at a high temperature of 600 °C. As with N, doping with S in the form of thiopenic sulfur has been shown to catalytically promote the conversion of LiPSs 13 .…”
Section: Resultsmentioning
confidence: 99%
“…increases the polarity of the carbon material and thereby enhances the adsorption of polar LiPSs and Li 2 S, improving long-term cycling stability 10,11 . Furthermore, recent studies have shown that N-and S-moieties do not have just an anchoring ability, but electrocatalytic activity thereby improving LiPS redox kinetics [12][13][14] .…”
mentioning
confidence: 99%